Legal Protection For Children In Interfaith Marriages: Comparative Study Between Indonesia And Other Countries - Martyana, Fina Puspita; Halim, Abdul (International Journal of Science and Society, 2024)
Interfaith marriage is a global phenomenon that raises various challenges, including in the context of legal protection for children. In Indonesia, this issue is becoming increasingly important considering the diversity of religions and beliefs held by its people, which requires an inclusive and fair legal approach. Comparative studies between Indonesia and other countries in terms of legal protection for children in interfaith marriages are important to identify best practices that can be adopted and adapted. This research aims to explore and compare the legal framework for child protection in interfaith marriages in Indonesia with other countries, to identify lacuna and provide policy recommendations. This research uses a normative legal approach with comparative studies, collecting data from various relevant sources and processing it to obtain significant findings. The research conclusions show that an inclusive and effective legal framework, along with efficient implementation, is the main key to ensuring the protection of children's rights in the context of interfaith marriages. Indonesia needs to adopt and adapt best practices from other successful countries in this regard, including strengthening the legal framework, increasing public education and awareness, and establishing effective support mechanisms. Through collaboration between stakeholders and active community participation, a more inclusive and supportive environment for children from interfaith marriages can be created. This ensures that their rights and welfare are thoroughly protected. It is hoped that the resulting policy recommendations can help strengthen child protection in interfaith marriages in Indonesia.